The Pemilihan Rute Distribusi Customer PT Java Agro Sari Berdasarkan Metode Algoritma Djikstra dan Saving Matrix - Yusuf Khoirul Huda; Elly Wuryaningtyas Yunitasari; Kusmendar Kusmendar (Program Studi Teknik Industri Universitas Setia Budi, 2024)
In customer distribution at PT Java Agro Sari, there are delays in delivery to customers. It even exceeds the accepted allowance time of 15 to 20 minutes. The purpose of this study is to determine the shortest distribution route so as to reduce delivery delays. In the delivery of PT Java Agro Sari's distribution to 13 customers A-B-C-D-E-F-G-H-I-J-K-L-M is divided into 2 routes, namely route 1 with customer A-B-C-D-E-F while route 2 with customer G-H-I-J-K-L-M which will determine the shortest distribution route. In determining the shortest distribution route using the Djikstra Algorithm and Saving Matrix methods, route 1 of the closest method of Djikstra Algorithm and Nearest Neighbor is obtained with the route sequence PT-A-C-E-F-D-B-PT with a total distance of 25.8 km. For route 2, the closest method is Algortima Djikstra with the route sequence PT-G-I-J-K-L-M-H-PT with a total distance of 46.1 km. From the research results, the methods that are more dominant in determining the shortest route are Djikstra Algorithm and Nearest Neighbor, PT Java Agro Sari should suggest modifications based on these methods to obtain the shortest distribution route so that it will save transportation costs which will affect profits for the company and make the price of its products more affordable because of the lower transportation costs.